Record and Watch for Improving Students’ Public Speaking - Zul Amri (Universitas Negeri Padang, 2014)
Public Speaking is a subject offered to the students of English Department, Faculty of Languges and Arts, Universitas Negeri Padang. Teaching the subject is sometimes found boring for both students and lecturer. Many students have slow progress and lack of interest in the subject. Many students find this subject scary because they have to do presentation several times while they are not ready for that. “Record and Watch” is an effective activity to improve their skills in Public Speaking. After implementing the activity for four times, the positive result begins to show up. Most of the students show their better interest at the subject indicated by the fact that many of them participate actively in the teaching and learning process. In addition, they also show improvement in English language accuracy and fluency indicated by fewer mistakes they have in their grammar and pronunciation and less hesitation in their presentations.